Effect of temperature on electrical conductivity in industrial effluents - Mandal, Harashit Kumar (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> This study is to know the effect of temperature on electrical conductivity in industrial effluents and sewages of Phagwara Tehsil of Punjab. Water contamination is a major global problem which requires ongoing evaluation and revision of water resources policy at level (Ugbune 2011). It has been suggested that it is the leading worldwide cause of deaths and disease (Pink 2006). Temperature increase was recently considered as a serious water pollutant. Increase in temperature can have adverse affect on the physical properties of water, such as density, viscosity, vapor pressure, surface tension, gas solubility and gas diffusion etc. Electrical conductivity (EC) is a measure of the ability of water sample to conduct electricity and is also related to the concentration of ionized substance in water. Temperature also has an important effect on conductivity. This is because as temperature increase, conductivity also increases owing to a decrease in viscosity that is caused by increase in temperature. The objective of this study is to know the level & effect of temperature on electrical conductivity in industrial effluents. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->